2018
DOI: 10.17711/sm.0185-3325.2018.005
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in terminal cancer inpatients: short-term survival and missed diagnosis

Abstract: Introduction. Delirium is a neurocognitive disorder, frequently present in advanced cancer patients. It morbidity, mortality, health expenditure, and causes distress to patients, family members, and health care professionals. Despite its impact, the disorder is still underdiagnosed, and consequently, mistreated. Objective. To describe the prevalence, clinical features, impact on the survival and percentage of missed diagnosis of delirium, in palliative care inpatients treated in a tertiary center. Method. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Delirium can be considered as a common syndrome of loss of consciousness in patients with advanced cancer [ 27 , 28 ]. In this study, 20.83% of the patients indicated expectant symptoms on admission, which was similar to the 26.0%~44.0% reported [ 29 ]. Current studies believe that the emergence of delirium is the result of multiple clinical factors, including drugs, electrolyte disorders, endocrine disorders, hypoxemia, infection, paraneoplastic syndrome, intracranial metastasis, and dehydration [ 30 ], although the study reported that through appropriate intervention, the outlook of nearly 50% of patients with advanced cancer is reversible.…”
Section: Discussionsupporting
confidence: 89%
“…Delirium can be considered as a common syndrome of loss of consciousness in patients with advanced cancer [ 27 , 28 ]. In this study, 20.83% of the patients indicated expectant symptoms on admission, which was similar to the 26.0%~44.0% reported [ 29 ]. Current studies believe that the emergence of delirium is the result of multiple clinical factors, including drugs, electrolyte disorders, endocrine disorders, hypoxemia, infection, paraneoplastic syndrome, intracranial metastasis, and dehydration [ 30 ], although the study reported that through appropriate intervention, the outlook of nearly 50% of patients with advanced cancer is reversible.…”
Section: Discussionsupporting
confidence: 89%
“…47 Most studies included inpatient specialist palliative care units in hospitals (n = 21) 32,37,39,41,42,44,46,[48][49][50][51][52][53][55][56][57][58][59][60][61][62] or hospice (n = 5). 33,39,47,51,54 Three studies each included palliative care consultation teams 40,45,49 and palliative care community services 33,41,43 In 23 studies, all participants had a primary cancer diagnosis, 32,33,37,[40][41][42][46][47][48][49][50][51][52][53][54][55][56]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…39,45 Participants in 24 studies were in the late stages of illness (e.g. advanced or terminal cancer), 32,33,37,[39][40][41][42][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] while in the remaining four studies participants' stage of illness was unclear. 39,[43][44][45] In 14 studies, only cross-sectional data was eligible for the review.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite common, this condition is underdiagnosed in health organizations; authors have stated that the incidence of this syndrome in intensive care units (ICUs) varies from 5% to 92% (6) . A study have suggested that the incidence of these cases in patients with cancer is high, and can reach 80% in more advanced stages of the disease, being related to a worst control of pain and to a diminution of survival rates (7) . In cancer patients, many studies reported associations between delirium, hospital mortality, and post-discharge mortality; in the last months of life, there is an association between its hypoactive and mixed subtypes and a lower survival rate (8) .…”
Section: Introductionmentioning
confidence: 99%